Analysis of the implementation of educational management policies on the workload of certified teachers at public junior high schools in Rengat Barat district, Indragiri Hulu regency - Citra Ayu; Isjoni; Azhar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research focuses on studying the implementation of education management policies regarding teacher workload at the certified junior high school (SMP) level. The research aims to determine the implementation of education management policies regarding the workload of accredited teachers in State Middle Schools and West Rengat District, Indragiri Hulu Regency so they will know the solution. This research uses a qualitative approach to field observation. The key information in this research is the people who are directly involved and know about teacher workload problems, namely the Regional Coordinator for Education and Culture, Heads of State Middle Schools, Deputy Heads, and teachers of State Middle Schools in West Rengat District, Indragiri Hulu Regency. Data collection techniques use interview techniques, documentation techniques, and observation techniques. Then, the data analysis process is carried out in four stages: data collection, data reduction, data presentation, and data verification or conclusion.